Consecutive Hypoalbuminemia Predicts Inferior Outcome in Patients With Diffuse Large B-Cell Lymphoma - Wei, Xiaolei; Zheng, Jingxia; Zhang, Zewen; Liu, Qiongzhi; Zhan, Minglang; Huang, Weimin; Chen, Junjie; Wei, Qi; Wei, Yongqiang; Feng, Ru (Frontiers in Oncology, 2021)
The prognostic value of albumin changes between diagnosis and end-of-treatment (EOT) in diffuse large B-cell lymphoma (DLBCL) remains unknown. We retrospectively analyzed 574 de novo DLBCL patients treated with R-CHOP from our and other 2 centers. All patients were divided into a training cohort (n=278) and validation cohort (n=296) depending on the source of the patients. Overall survival (OS) and progression-free survival (PFS) were analyzed by the method of Kaplan-Meier and Cox proportional hazard regression model. In the training cohort, 163(58.6%) patients had low serum albumin at diagnosis and 80 of them were present with consecutive hypoalbuminemia at EOT. Patients with consecutive hypoalbuminemia showed inferior OS and PFS (p=0.010 and p =0.079, respectively). Similar survival differences were also observed in the independent validation cohort (p=0.006 and p=0.030, respectively). Multivariate analysis revealed that consecutive hypoalbuminemia was an independent prognostic factor OS (relative ratio [RR], 0.455; 95% confidence interval [CI], 0.291-0.711, p =0.001) and PFS (RR, 0.508; 95% CI, 0.361-0.693, p<0.001) in all DLBCL patients independent of IPI. In conclusion, consecutive hypoalbuminemia is a simply and effectively adverse prognostic factor in patients with DLBCL, which remind us to pay more attention to patients with low serum albumin at EOT during follow up.